Use of dynamic adaptive chemistry and dynamic cell clustering in computational fluid dynamics to accelerate calculation of combustion simulation of diesel engine - Feng, Shiquan; Zhang, Hongmei (Fuel (Guildford), 2023)
•Effects of dynamic adaptive chemistry and dynamic cell clustering has been examined at several working conditions.•The threshold value of DAC should not be too small.•The two parameters of DCC will affect the formation of NOx and soot.•Both DAC and DCC can reduce the time required for calculation and can be applied together. Based on the theory of dynamic adaptive chemistry and dynamic cell clustering, a 3D model for fuel combustion in the cylinder is constructed to study the fast calculation algorithm to accelerate the engine combustion simulation and analyze the impacts of the basic structure and the main parameters of dynamic adaptive chemistry and dynamic cell clustering on diesel engine simulation. It is found that the error threshold value of the dynamic adaptive chemistry algorithm should be set appropriately to ensure the accuracy of the simulation, and the dynamic adaptive chemistry algorithm should employ different initial search species and threshold values to meet different research objectives. Regarding the dynamic cell clustering algorithm, the data accuracy in the overall spatial range can be guaranteed, but the local location information will be missing, which will have a great impact on the prediction of pollutants. Therefore, suitable cell clustering conditions should be selected to meet the requirements of different targets.